Anti-Allergic Effect of Ulmus davidiana Cortex on Contact Dermatitis Induced by Dinitrofluoro- Benzene in Mice - Lyu Jeonghyeon; Kim Byung-Joo; Kim Hyungwoo (Korean Pharmacopuncture Institute, 2013)
Objective: The root bark of Ulmus davidiana var. Japonica (Ulmi Radicis cortex, URC) is a medicinal herb used for promoting diuresis and treating dampness. In Korea, URC has long been used as an efficacious therapy for inflammation, burns, frostbite and skin diseases such as eczema and psoriasis. Methods: In the present study, we used 1-fluoro-2,4- dinitrofluorobenzene (DNFB)-induced contact dermatitis (CD) mouse model to investigate the antiallergic and the anti-inflammatory effects of URC on skin lesion, histopathological changes and specific antibody production. Results: URC treatment, 10 mg/mL, effectively inhibited skin lesions induced by repeated paintings with DNFB. In the histopathological observation, topical application of URC inhibited spongiosis. In addition, URC lowered the production levels of total immunoglobulin and IgG2a in serum. Conclusion: These data indicate that URC has an anti-inflammatory effect that produces an improvement of skin lesions in CD mice.